Halfway Through Ex Situ Population Genetic Lifespan: The Case of Cochlearia polonica - Anna Rucińska; Katarzyna Joanna Chwedorzewska; Piotr Tomasz Bednarek; Maja Boczkowska; Jerzy Puchalski; Piotr Androsiuk; Ewa Czaplicka (Biology)
Although the usage of genetic data for the conservation management of threatened species is growing rapidly, the assessment of the trajectory and persistence of ex situ and in situ populations suffers from a lack of monitoring of genetic indicators. To fill this gap, we conducted a comparative analysis of the genetic structure ex situ and its source population of Cochlearia polonica to improve conservation outcomes for this species. C. polonica, as a range-restricted endemic species in Poland, exists in the wild in a single reintroduced population, which was the source for establishing an ex situ population in the botanical garden, and both populations have been well studied in abundance time series until the extinction of artificial populations due to genetic constraints. We collected AFLP data from individuals sampled after the peak recovery phase following the founder effect in the ex situ population, as well as from the source population, to assess the genetic consequences of long-term cultivation. The genetic profile of both populations suggested their strong differentiation. The genetic variation in the ex situ population expressed by Shannon’s Information Index and expected heterozygosity (He) was approximately half that of the source population. While ex situ population growth was high, the gene pool was homogenised, and genetic diversity waned, leading to its extinction across merely 5–6 generations. Thus, the only reintroduced population of C. polonica left in the wild is more threatened with extinction than previously thought, and conservation action should be taken immediately.